The reperatoire of Bodra smyana choir in the 40s – 70s of the 20th century - Georgieva, Iva (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
In the history of „Bodra Smyana“ choir, conducted by Boncho Bochev, there are three stages, during which some smooth changes are noticed in the repertoire of the choir. The Bulgarian composers, mostly contemporary, occupy a central place. During the different stages of its development, the choir performs songs by the composers involved in the choral work: Dobri Hristov, Svetoslav Obretenov, Lyubomir Pipkov, Georgi Dimitrov, Dimitar Petkov, Todor Popov and others. The circle of foreign authors, at first predominantly Russian and Slavic, gradually encompasses the western classics and pre-classics: Monteverdi, Pergolesi, Bach, Bela Bartok, Zoltan Kodaly, Kabalevsky and others. Including varied genre and thematic content, Boncho Bochev’s successful repertoire policy is raising the choir on a world level.